HUBUNGAN ANTARA TINGKAT STRES DENGAN PERILAKU MEROKOK PADA MAHASISWA FAKULTAS TEKNIK UNIVERSITAS SAM RATULANGI - Bawuna, Noni Hilda; Rottie, Julia; Onibala, Franly (JURNAL KEPERAWATAN, 2017)
Abstract : Stress is the reaction or the body's response to psychosocial stressors of mental stress or life burden, the classification of stress levels among others, mild, moderate, and severe stress. Smoking behavior is an activity done by individuals in the form of burning and sucking it and can cause smoke that can be inhaled by the people around himThe purposeof this study to analyze the relationship between stress levels with smoking behavior in students of the Faculty of Engineering Sam Ratulangi University. The research method is descriptive analytic retrospective study design. The sampling technique in this research is purposive sampling in this research is total sampling with 61 samples. The data collection is done by using a questionnaire and interview sheet. Processing data using computer program with Pearson chi-square test with a significance level of 95% (Î± =, 005). ). The results using the Pearson chi-square analysis showed a significant correlation between the stress level and smoking behavior on the students (p = 0,000). Conclusion there is correlation between stress level with smoking behavior at student of Faculty of Engineering Sam Ratulangi University. Keywords:stress level, smoking behavior Abstrak : Stres adalah reaksi atau respons tubuh terhadap stressor psikososialtekanan mental atau beban kehidupan, klasifikasi tingkat stress diantaranya, stress ringan, sedang, danberat. Perilaku merokok adalah sesuatu aktivitas yang dilakukan individu berupa membakar dan menghisapnya serta dapat menimbulkan asap yang dapat terhisap oleh orang-orang disekitarnya Tujuan penelitian ini untuk menganalisa hubungan antara tingkat stress dengan perilaku merokok pada mahasiswa Fakultas Teknik Universitas Sam Ratulangi. Metode penelitian yaitu deskriptif analitik dengan rancangan study retrospektif. Teknik pengambilan sampel pada penelitian ini purposive sampling. Pengumpulan data dilakukan dengan menggunakan kuesioner dan lembar wawancara. Pengolahan data menggunakan program computer dengan uji pearson chi-square dengan tingkat kemaknaan 95% (Î±= ,005). Hasil penelitian dengan menggunakan analisis pearson chi-square menunjukkan terdapat hubungan signifikan tingkat stress dengan perilaku merokok pada mahasiswa (p= 0,000). Kesimpulan terdapat hubungan antara tingkat stress dengan perilaku merokok pada mahasiswa Fakultas Teknik Universitas Sam Ratulangi. Kata kunci : Tingkat stres, Perilaku Merokok